A New Approach To Improving The Professional Skills And Personal Qualities Of Foreign Language Teachers In Higher Education Countries - Anvarov, Alijon Uktamovich (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article considers a new approach to improving the professional skills and personal qualities of professors and teachers teaching foreign languages ​​in higher education. Information is provided on the need for a modern teacher of higher education to have a high level of professional knowledge of his subject and to have modern technical means of teaching. The article also provides recommendations on the methodology for teaching professional foreign languages ​​to higher education students at a high level.